2021
DOI: 10.1016/j.techfore.2020.120521
|View full text |Cite
|
Sign up to set email alerts
|

Impact of technological innovation on energy efficiency in industry 4.0 era: Moderation of shadow economy in sustainable development

Abstract: Despite the ongoing research on energy efficiency and innovation in the context of Industry 4.0, little is known on how degree of leakages in economy can impact the energy efficiency-innovation association. This issue has been addressed by the United Nations in their Sustainable Development Goals (SDG) report also. In the era of Industry 4.0, this issue can be crucial from the perspective of sustainable development, and we are analyzing this issue in case of Middle East and North African (MENA) countries over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(105 citation statements)
references
References 57 publications
3
75
0
4
Order By: Relevance
“…The EKC hypothesis also considers the role of additional factors such as natural resources, globalization, and energy innovations or demographic changes, i.e., the ageing population (Dooley 1998). Current studies have considered that energy innovation is the main key driver behind the decline in global warming and assurance of sustainable economic growth (Balsalobre and Álvarez 2016, Álvarez et al 2017, Chen et al 2021. Torras and Boyce (1998) demonstrated that energy innovations improve environmental quality, thereby attributing technical effect as the central feature in plummeting ambient pollution (Aghion et al 2014).…”
Section: Energy and Environmental Degradationmentioning
confidence: 99%
“…The EKC hypothesis also considers the role of additional factors such as natural resources, globalization, and energy innovations or demographic changes, i.e., the ageing population (Dooley 1998). Current studies have considered that energy innovation is the main key driver behind the decline in global warming and assurance of sustainable economic growth (Balsalobre and Álvarez 2016, Álvarez et al 2017, Chen et al 2021. Torras and Boyce (1998) demonstrated that energy innovations improve environmental quality, thereby attributing technical effect as the central feature in plummeting ambient pollution (Aghion et al 2014).…”
Section: Energy and Environmental Degradationmentioning
confidence: 99%
“…In addition, it leads to company internal innovations and improved competitiveness [97]. While it is well researched at the level of a company or a state [98,99] it has not yet been investigated at a regional economy level. Energy security and energy efficiency goals at a national level are determined by the strategic interest of a country [84].…”
Section: Innovation In the Energy Sector In Russiamentioning
confidence: 99%
“…The share of enterprises/companies that undertook technological and organizational innovations in the reporting year of the total number of organizations surveyed was our second indicator representing the introduction of innovation stage (Y2). In this research, we used the open data of the Russian Federal State Agency Russian Export Center [98] on high-tech exports (it does not include raw materials and energy) to calculate the following:…”
Section: Innovation Indicatorsmentioning
confidence: 99%
“…The development of energy is also relevant in the context of the Fourth Industrial Revolution (Industry 4.0), as evidenced by the work [7]. Among scientists, technological innovations in energy supply systems based on the principles of sustainable development deserve attention [8]. By the way, researchers have identified the role of Industry 4.0 in ensuring sustainability [9].…”
Section: Issn 2664-9969mentioning
confidence: 99%